Are tools all we need? Digital Humanities in the time of its institutionalisation - Monella, Paolo (Testo e Senso, 2011)
Three key features of the Digital Humanities today are its quantitative growth, its institutionalisation and its definition as a discipline. In the first part of this article (2. Institutional models) I shall pinpoint some models of institutionalisation that are emerging in the international scenario. Against this background, I shall then discuss (3. Tools) some concepts central to Digital Humanities’ self-definition, such as those of practice, ‘building’, centre, project, product and tools, particularly questioning the opinion that the creation of friendly digital tools is the key issue in the future of the field. I shall finally suggest that ‘instrumentalism’, ‘project fever’ and an excessive focus on friendly tools should not get the upper hand over the methodological work necessary to build digital applications which possess real added value by comparison with traditional research practices. — Tre caratteri salienti dello sviluppo attuale dell’Informatica umanistica sono la sua crescita quantitativa, la sua istituzionalizzazione e la sua definizione disciplinare. Nella prima parte di questo articolo (2. Institutional models) vengono passati in rassegna alcuni modelli istituzionali emergenti nel quadro internazionale. In questo quadro vengono dunque discussi (3. Tools) alcuni concetti chiave nella riflessione sulla disciplina, come quelli di pratica, ‘building’, centro, progetto, prodotto e strumento. In particolare, si contesta che la creazione di strumenti digitali ‘user-friendly’ costituisca il nodo fondamentale per lo sviluppo della disciplina. Bisogna infatti evitare che da un lato un approccio strumentale all’Informatica umanistica, dall’altro strategie di ricerca esclusivamente fondate su singoli progetti e sullo sviluppo di strumenti ‘friendly’, distolgano dal lavoro metodologico necessario per elaborare metodologie informatiche dotate di un reale valore aggiunto rispetto alle pratiche tradizionali della ricerca.